ANTI-INFLAMMATORY ACTIVITY OF MARINE SPONGE CALLYSPONGIA SP. AND ITS ACUTE TOXICITY - ADRYAN FRISTIOHADY; WAHYUNI WAHYUNI; FADHLIYAH MALIK; LA ODE MUHAMMAD JULIAN PURNAMA; BARU SADARUN; SAHIDIN I (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study aims to investigate the anti-inflammatory effect of the ethanolic extract of Callyspongia sp. using stabilization of the human red blood cell (HRBC) membrane method and its acute toxicity using brine shrimp lethality test (BSLT) method. Methods: Callyspongia sp. was macerated with 96% ethanol. Extract characterized and screened for the secondary metabolite. Anti-inflammatory activity by stabilization of the HRBC membrane method with a varied dose of 50 ppm; 100 ppm; 200 ppm; 400 ppm; 800 ppm; 1600 ppm; and 3200 ppm. Solutions observed using a photometer to describing stability and ability in preventing membranes hemolytic and statistically analyzed using SPSS. Acute toxicity carried out by the BSLT method and analyzed using Minitab®ver. 17.2.1. Results: The phytochemical screening was indicating that Callyspongia sp. contains flavonoid, alkaloid, and terpenoid. The results of the anti-inflammatory activity test showed that the percentage value of stability and hemolysis of extracts with doses of 50, 100, 200, 400, 800, 1600, and 3200 ppm were 55% and 45%, 63% and 37%, 70% and 30%, 74% and 26%, 80% and 20%, 87% and 13%, and 97% and 3%, respectively. It showed that extract of sponge Callyspongia sp. in all varied dose has activity in stabilizing the HRBC membrane thus can be potential as an anti-inflammatory. The results of acute toxicity assay showed that the value of LC50 was 1281.45 μg/ml and categorized as nontoxic to Artemia salina Leach. Conclusion: Various concentrations of Callyspongia sp. effective as an anti-inflammatory in stabilizing HRBC, and categorized as safe.